O REUNI NA UFMA E O FAVORECIMENTO DO ACESSO DE ALUNOS COM DEFICIÊNCIA AO ENSINO SUPERIOR: questões para reflexão - Martins, Vivianne da Silva Braga (2012)
This research addresses facilitating access to higher education for students with disabilities enrolled by the quota system, from the accession of the Federal University of Maranhão (UFMA) Program Plan Support and Restructuring Jobs in Public Universities (REUNI) the period 2007 to 2012. The aim of this study was to examine whether the accession of the UFMA REUNI favored or not the access of students with disabilities in higher education enrollment rates observed these students. The specific objectives defined: compare rates of admission of students with disabilities to graduate courses of UFMA after the accession of the IES REUNI; identify the types of disabilities and the courses chosen by students with disabilities after the accession of the UFMA REUNI; verify the REUNI is a social inclusion policy to higher education for people with disabilities by expanding the number of vacancies and identify whether the measures adopted by UFMA to improve access for a larger number of vacancies include program guidelines REUNI. The research was exploratory and descriptive. As for the means, this study was characterized as literature and documents, using primary sources, official government documents, guidelines REUNI, the management plan UFMA, the Guidelines on UFMA REUNI. It found a significant increase in the number of vacancies in undergraduate courses of UFMA between 2007 and 2012, and the presence of quotas for enrollment by students with disabilities in constant growth, mainly from 2010. It was found that the results show that from REUNI students with disabilities had more opportunity to move up a degree course in UFMA. With the accession of the UFMA REUNI, there was a transformative impact practical, what came to contribute to this IES fulfill its institutional mission, continuing the historical aspirations of education, development and citizenship.